Steel for offshore wind turbines of class 32 kg with high modulus of elasticity and method for its production
Patent Information
- Application Number
- CN202611375349.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-13
AI Technical Summary
但其主要技术路径聚焦于厚度、成材率与韧性控制,其不足之处在于,未考虑刚度设计,未涉及海上风电结构模态响应调控所需的钢材高弹性模量性能
[0047](1)本发明通过采用低C、Mn+Sn-Sb耐海洋大气腐蚀合金化+Ti-B原位析出增强相+Nb微合金化的成分设计,在低C、低Mn体系保证高铁素体比例和良好的塑性储备基础上,控制Sn/Sb质量比为0.60~2.00以形成稳定、均匀的耐蚀锈层,并通过Nb微合金化细化组织。
Smart Images

Figure CN122898808A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metallic materials, and in particular relates to a 32kg grade marine atmospheric corrosion resistant structural steel for offshore wind power with high elastic modulus and its manufacturing method. Background Technology
[0002] As a strategic emerging industry for achieving green energy transformation and high-quality development, offshore wind power is rapidly expanding its installed capacity and application scenarios to deep-sea areas. Compared to onshore wind power, offshore wind power equipment faces more complex natural environments and more stringent structural safety challenges during operation, including the combined effects of strong wind loads, wave impacts, hydrodynamic interference, sea ice loads, tidal forces, and long-term corrosion from multiple sources. These external environmental conditions require wind turbine structures to possess higher stiffness control capabilities, deformation stability, and operational reliability throughout their entire lifecycle. With the continuous increase in the power of offshore wind turbines and the expansion of their overall size, the total tower height of megawatt-class wind turbines often exceeds 140 meters, the hub center height continues to rise, and the rotor diameter even exceeds 120 meters. This massive structural system needs to maintain overall coordinated deformation and local vibration resistance under multi-axis coupled loads to avoid structural instability such as resonance, instability, or stress concentration failure. This complex dynamic behavior places higher demands on the stiffness characteristics of materials, especially the elastic modulus.
[0003] The elastic modulus is a fundamental parameter that measures a material's ability to undergo elastic deformation under unit stress, directly determining the stiffness level and first-order natural frequency of structural components. In critical structures such as wind turbine towers, jacket structures, and pile foundations, increasing the material's elastic modulus not only helps control overall deformation but also effectively raises the structure's natural frequency, reducing the risk of resonance between wind-induced and wave-induced excitation and the structure's natural modes. This reduces fatigue accumulation effects and vibration amplitude, extending service life. Furthermore, high-elastic-modulus steel can also offer significant cost-saving and efficiency-enhancing potential by reducing structural wall thickness or increasing stiffness per unit mass. However, the elastic modulus is an intrinsic property of a material, primarily determined by interatomic bonding forces and crystal structure. Traditional alloy composition design, rolling, or heat treatment processes cannot significantly alter this intrinsic property of steel. Therefore, the difficulty in achieving stiffness enhancement with traditional wind power steel has become one of the core factors restricting the optimization of wind power equipment structural design.
[0004] While structural steels widely used in current engineering practice meet basic structural requirements in terms of strength and toughness—for example, existing DH32, EH32, and similar structural steels mainly achieve a balance between strength and toughness through C-Mn low alloying and controlled rolling and cooling—their elastic modulus is typically in the range of 200–210 GPa. For thin to medium-thick steel plates in the upper section of towers, simply increasing strength cannot simultaneously solve the problem of insufficient stiffness; if stiffness is compensated by increasing wall thickness, it will increase self-weight, welding workload, and transportation and installation burdens.
[0005] Currently, relevant domestic and international standards such as GB / T 1591 "Low-alloy High-strength Structural Steel", GB / T 712 "Structural Steel for Ships and Marine Engineering", EN10025, and EN10225 have provided general strength grades of steel foundations for wind power structures. However, a systematic design and material matching system has not yet been formed for stiffness performance indicators. The lack of systematic optimization and clear constraints on the elastic modulus parameter in existing material systems limits further improvements in high-order dynamic response control, overall stiffness enhancement, and stability under ultimate loads for wind power structures.
[0006] In summary, developing a series of wind turbine structural steels with high elastic modulus and excellent comprehensive mechanical properties has become an urgent need for the current development of offshore wind power equipment materials technology. By constructing a series of high elastic modulus steel products ranging from low to high strength grades, and configuring material performance according to the strength and stiffness requirements of different structural parts such as the upper transition section of various offshore wind turbines, maintenance platform supports, pile foundation uppers, pile foundation nodes, X-joints, suction cylinders, jacket structures, and tendon tubes, it is possible to significantly improve structural response control capabilities, enhance service stability, and provide key material support for offshore wind power equipment to move towards higher power, larger scale, and farther sea areas. The construction of this material system will play a vital role in improving the operational reliability and industrial competitiveness of offshore wind power equipment.
[0007] Public reports on related patents:
[0008] Chinese invention patent CN114686783B discloses a high-elasticity modulus age-hardening high-speed steel material and its preparation method. It employs a multi-element high-alloy system, using solid solution strengthening by adding Cr, V, Ni, and the non-metallic element N, as well as synergistic particle reinforcement by adding nitrides. Combined with powder metallurgy + high-temperature solid solution + aging treatment processes, a high-elasticity modulus age-hardening high-speed steel with an elastic modulus greater than 240 GPa is obtained. This method uses high-temperature heat treatment to form a dispersed phase to enhance stiffness, making it suitable for the cutting tool and mold fields. However, due to its primary use of powder metallurgy, its complex composition, high processing temperature, and high cost make it difficult to meet the engineering adaptability requirements of wind power structural steel in large-scale continuous casting-hot rolling production and low-cost manufacturing.
[0009] Regarding the performance requirements of steel used in offshore wind turbine structures, numerous inventions in recent years have focused on optimizing the composition system and heat treatment process to improve the fracture toughness, thickness-direction properties, and resistance to aging. For example, Chinese invention patent CN111809117A discloses a high fracture toughness, low aging sensitivity offshore wind turbine steel and its production method. It employs a C-Si-Mn-Nb-Ti-Mo-Ni composition system and utilizes a process path of continuous casting + two-stage controlled rolling + UFC / ACC controlled cooling + hot straightening + heat sink cooling to achieve excellent CTOD and low-temperature aging properties. The maximum thickness of the finished product reaches 130 mm, and the maximum weight of a single continuously cast billet reaches 32 tons. This solution focuses on improving the safety of welded joints and service aging stability. While it significantly controls the microstructure and toughness, it does not propose a design mechanism to increase the material's elastic modulus to enhance structural stiffness.
[0010] Chinese invention patent CN111676424A discloses a method for producing heavy-duty, extra-thick steel for offshore wind power. By employing a process route of continuous casting + heating + controlled rolling + pre-straightening + controlled cooling + slow cooling, it achieves a good balance of strength and toughness, as well as stable microstructure, up to a maximum thickness of 130mm. This invention achieves homogenized microstructure by optimizing the rolling reduction rate and cooling rate, resulting in excellent weldability while meeting the requirements for heavy-duty and extra-thick steel. However, its main technical approach focuses on thickness, yield, and toughness control. Its shortcoming lies in the lack of consideration for stiffness design and the absence of addressing the high elastic modulus properties of the steel required for modal response regulation of offshore wind power structures.
[0011] Chinese invention patent CN110846554A discloses a manufacturing method for EH32 grade marine engineering steel and steel plates with high ductility. It employs a C-Si-Mn low-alloy system and LF / RH refining, protective casting, and controlled rolling and cooling processes to achieve high ductility, low-temperature toughness, and fracture toughness, with an elongation ≥33%, impact energy ≥200J at -40℃, and NDTT temperature ≤-40℃. This solution serves the collision safety requirements of ships and marine engineering. However, its shortcomings include the lack of consideration for the elastic modulus of steel used in the upper and middle sections of offshore wind turbine towers, and the absence of a compositional design addressing resistance to marine atmospheric corrosion and the elastic modulus.
[0012] In summary, current high-elasticity modulus steel and offshore wind power steel, as well as their manufacturing technologies, have the following shortcomings:
[0013] 1. Currently, most publicly available high elastic modulus steel technologies employ high alloying elements, intermetallic compounds, and complex powder metallurgy processes, which increases the manufacturing cost of materials and makes it difficult to meet the needs of mass production of offshore wind power equipment.
[0014] 2. Existing high elastic modulus steels are mainly used in automobiles, cutting tools, molds and dies, etc., mainly in cold-rolled thin plates or small-sized products. They do not involve the service performance required in marine environments such as low-temperature impact toughness and corrosion resistance. They are difficult to meet the thickness specifications of large structural components for offshore wind power, and it is also impossible to evaluate the service safety of materials in marine environments.
[0015] 3. Existing research on offshore wind power steel and marine engineering structural steel of similar strength grade mainly focuses on strength, low temperature toughness, Z-direction performance, weldability, ductility or production stability of thick specifications. The modulus of elasticity has not yet been used as a clear material indicator for the stiffness and modal response of wind power structures. This makes it difficult to meet the structural safety and stiffness requirements brought about by the further development of offshore wind power equipment towards deep sea, high power and large size. Summary of the Invention
[0016] The purpose of this invention is to overcome the above-mentioned problems and deficiencies and provide a 32kg grade offshore wind power steel with an elastic modulus ≥220GPa, yield strength ≥320MPa, tensile strength 440~570MPa, elongation after fracture ≥21%, and Charpy impact energy ≥100J at -20℃. This 32kg grade offshore wind power steel with high elastic modulus has high elastic modulus, resistance to marine atmospheric corrosion, and good low-temperature toughness and elongation, as well as its production method. It is suitable for the upper section, middle and upper section cylinder and other structures of offshore wind turbine towers.
[0017] The objective of this invention is achieved as follows:
[0018] A 32kg grade offshore wind power steel with high elastic modulus has the following composition by weight percentage: C: 0.03%~0.04%, Si: 0.15%~0.25%, Mn: 0.90%~1.00%, Sn: 0.05%~0.12%, Sb: 0.05%~0.10%, Nb: 0.015%~0.025%, Ti: 1.5%~2.5%, B: 0.6%~1.2%, P: ≤0.01%, S: ≤0.002%, Als: 0.015%~0.025%, with the remainder being Fe and unavoidable impurities.
[0019] Furthermore, in the wind power steel, -0.6%≤Ti-2.22×B≤0.6%.
[0020] Furthermore, the Sn / Sb ratio in the wind power steel is 0.60~2.00.
[0021] Furthermore, the microstructure of the wind power steel includes ferrite and pearlite, with fine TiB2 hard reinforcing particles uniformly dispersed throughout the steel.
[0022] Furthermore, the ferrite volume percentage is 80%~90%, the average ferrite grain diameter is about 11~16μm; the pearlite lamellar spacing is ≤200nm; the TiB2 hard reinforcing particles in the wind power steel have a volume fraction ≥3%, an average particle size <5μm, and a distribution density of 1000~2000 particles / mm².
[0023] The steel plate used for offshore wind power has an elastic modulus ≥220GPa, yield strength ≥320MPa, tensile strength 440~570MPa, elongation after fracture ≥21%, Charpy impact energy at -20℃ ≥100J, and a thickness range of 20~60mm.
[0024] The rationale for the design of the components in this invention is as follows:
[0025] The overall design concept of this invention is as follows: First, focusing on the coupled requirements of stiffness, low-temperature toughness, and resistance to marine atmospheric corrosion in the upper and middle sections of 32kg-class offshore wind turbine towers (thin to medium-thick steel plates), a design with low C and Mn content is selected. This low C and Mn system ensures the ferrite phase ratio in the final microstructure of the steel plate, compensating for the plasticity loss caused by the introduction of hard reinforcing phase particles. Second, Sn and Sb are added, and the Sn / Sb mass ratio is controlled at 0.60~2.00, so that Sn is enriched to stabilize the rust layer and Sb is evenly distributed. The process involves several key aspects: First, the inhibition of Cl- penetration by the cloth synergistically enhances the steel plate's resistance to marine atmospheric corrosion and extends the service life of offshore wind power steel. Second, Nb microalloying significantly inhibits austenite grain growth and promotes ferrite refinement, thereby improving the overall strength, toughness, and microstructure uniformity of the steel plate. Third, the introduction of Ti and B elements, and the control of the Ti-to-B ratio (-0.6%≤Ti-2.22×B≤0.6%), ensures that the reinforcing phase forms in situ during the solidification of the molten steel and subsequent solidification microstructure evolution, maintaining a fine and dispersed distribution. By utilizing high-modulus particles to constrain composition, inclusions, solidification flow, rolling deformation, and phase transformation microstructure, an elastic modulus gain is achieved under 32kg-level strength, toughness, and corrosion resistance conditions, meeting the requirements of high-rigidity steel plates for large-scale offshore wind power structural design.
[0026] Carbon (C) is one of the fundamental elements ensuring the strength of the steel plate matrix. Although this invention uses a low-carbon system, C can still synergistically enhance the strength of the steel plate through solid solution strengthening and microalloying precipitation strengthening mechanisms. In this invention, the design role of C content is mainly reflected in the following three aspects: First, it contributes to the strength of the steel plate matrix through solid solution strengthening; second, it provides the necessary carbon source for the formation of NbC precipitates by working together with microalloyed Nb elements, thus pinning grain boundaries in the form of NbC precipitation to hinder austenite grain coarsening and providing favorable conditions for final microstructure refinement control; third, based on the perspective of phase structure control, it adopts the lowest possible C content to increase the proportion of soft ferrite phase, thereby compensating for the plasticity problem caused by the introduction of elastic modulus-enhancing phase particles. Therefore, considering the purpose of the invention and the overall performance, the preferred C content is controlled at C: 0.03%~0.04%.
[0027] Si is the main deoxidizing component in the steelmaking process. Si in solid solution form can increase strength, ductile-brittle transition temperature, elastic limit and fatigue strength. In order to obtain sufficient deoxidation effect, it must contain more than 0.10%. However, if the upper limit is too high, it will reduce the toughness of the base material and welded parts and have an adverse effect on the surface quality of the steel. Therefore, it is preferred to control the Si content at 0.15%~0.25%.
[0028] Mn: Mn is an essential element for ensuring the strength and toughness of steel. In this invention, the role of Mn is mainly reflected in two aspects: first, it contributes to the strength of the steel plate matrix through solid solution strengthening; second, Mn expands the austenite region, which can improve the hardenability of steel and is beneficial for controlling the pearlite lamellar spacing during rapid cooling of the steel plate. However, Mn is prone to segregation in steel, especially at 1 / 4 and 1 / 2 thickness of medium-thick steel plates, resulting in a significant reduction in low-temperature toughness and even delamination of the impact fracture surface. More importantly, as the Mn content increases, the corrosion resistance of the steel plate decreases. Therefore, considering both material mechanics and corrosion resistance, the preferred Mn content range is controlled between 0.90% and 1.00%.
[0029] Sn: Sn can increase the corrosion potential of steel and reduce the self-corrosion current density. By increasing the double-layer resistance and inhibiting ion exchange, it slows down the corrosion rate and improves corrosion resistance. After rust forms, the presence of SnO2 in the rust layer, along with the synergistic effect between Sn and Sb, can inhibit further dissolution of the steel and reduce the corrosion rate. However, excessive Sn content can impair the toughness of the steel and increase the risk of localized acid pitting corrosion; therefore, its content is controlled between 0.05% and 0.12%.
[0030] Sb: When added in combination with Sn to steel, it can improve the corrosion resistance of the steel, resulting in Sn enrichment and uniform Sb distribution in the rust layer. A SnO2-Sb2O5 corrosion-resistant oxide film is formed on the steel surface, enhancing its ability to block Cl- ion penetration. Therefore, it is particularly suitable for steels operating in Cl-rich marine atmospheric conditions. Furthermore, the addition of small amounts of Sn and Sb replaces expensive corrosion-resistant elements such as Cr, Ni, and Mo, which is beneficial for cost control. However, Sb has an adverse effect on the mechanical properties of steel, reducing its strength and increasing its brittleness. This invention controls the Sb content to be within the range of 0.05% to 0.10%. Preferably, the Sn / Sb mass ratio is controlled between 0.60 and 2.00. When the Sn / Sb ratio is too low, the relative enrichment of Sb may exacerbate grain boundary embrittlement and localized pitting corrosion sensitivity, weakening low-temperature toughness and stability. When the Sn / Sb ratio is too high, the enrichment tendency of Sn in grain boundaries and low-melting-point regions is enhanced, easily increasing the risk of hot-working cracks and localized acid corrosion. By controlling the Sn / Sb ratio within the above range, the two effects of Sn promoting the formation of a dense rust layer, Sb improving the uniformity of the rust layer, and Cl- blocking ability can be balanced, thus achieving a corrosion resistance effect suitable for marine atmospheric environments without relying on high-priced corrosion-resistant elements such as Cr, Ni, and Mo.
[0031] Nb: Nb is an important microalloying element used in this invention for microstructure refinement and performance enhancement. It has a strong affinity for non-metallic elements such as C, N, and O, and can form stable NbC, NbN, or Nb(C,N) micro-precipitates. During the hot working of steel plates, Nb effectively controls the microstructure of the rolled steel plate by inhibiting austenite grain growth, delaying dynamic recrystallization, and promoting ferrite phase transformation, significantly improving the refinement and uniformity of the microstructure, thereby enhancing the strength and toughness matching level of the steel plate. Especially under the single-pass high reduction rolling and low-temperature homogenization strategy adopted in this invention, NbC and other precipitates can act as grain pinning points, effectively improving rolling stability and controlling the final rolled microstructure morphology. Considering the good stability and grain control ability of Nb in the continuous casting + TMCP process, the Nb content is preferably controlled at 0.015%~0.025% in this invention to give full play to its microalloying refinement and strengthening effect, while avoiding coarsening of precipitates and increased costs due to excessive addition.
[0032] Ti: Ti is a key element in this invention for solidification stage microstructure control and target reinforcing phase construction. For 32kg grade low-C-Mn-Sn / Sb-Nb offshore wind power steel, if the Ti content is too low, it is difficult to form a sufficient number of fine TiB2 particles with B, resulting in unstable improvement in elastic modulus; if the Ti content is too high, it is easy to increase the risk of enrichment of coarse TiN, TiC, or unreacted Ti, causing billet segregation, toughness fluctuations, and decreased stability of the weld heat-affected zone. This invention designs Ti in conjunction with a low-C, low-Mn, high-ferrite matrix, electromagnetic stirring, and three-stage controlled rolling, so that TiB2 is formed in situ during continuous casting solidification and remains dispersed during subsequent high-pressure and controlled cooling processes, thereby contributing stiffness gain without sacrificing the elongation and low-temperature impact toughness of 32kg grade steel plates. Considering the stoichiometry required for TiB2 formation, steel reaction loss, inclusion control, and industrial continuous casting operability, the Ti content is preferably controlled within the range of 1.5% to 2.5%.
[0033] In this invention, element B is not used as a conventional trace hardenability element, but rather as a reactive component for in-situ TiB2 formation and a solidification structure regulator. When the B content is too low, the amount of TiB2 formed is insufficient, making it difficult to form a stable particle-reinforcing network; when the B content is too high, residual B may segregate at grain boundaries or form brittle boron-containing phases, reducing plasticity and low-temperature toughness. This invention controls B at 0.6%~1.2%, and together with the Ti content, satisfies -0.6%≤Ti-2.22×B≤0.6%, ensuring that Ti and B are consumed as much as possible in the form of target TiB2 particles under industrial continuous casting conditions. Simultaneously, long-term argon blowing at LF, RH refining, M-EMS / F-EMS, and partitioned secondary cooling suppress particle agglomeration and central segregation. This combination transforms the role of B from a single hardenability regulator to a high-modulus microstructure building factor that works synergistically with Ti, the solidification flow field, and the TMCP process, with its preferred content range being 0.6%~1.2%.
[0034] P (Polyphosphate) is a typical harmful impurity element in steel. During cooling and solidification, it easily segregates in the center of the slab and accumulates at grain boundaries to form a brittle thin film structure, significantly reducing the low-temperature impact toughness and ductility of the steel plate. It also exacerbates the crack sensitivity of the weld heat-affected zone, affecting the weldability of the steel. Although P can improve the atmospheric corrosion resistance of steel under certain conditions, its weakening effect on fatigue performance and overall ductility and toughness is more significant, making it difficult to use as a corrosion-resistant alloying element in high-strength and toughness structural steels. The steel plate of this invention has achieved improved corrosion resistance to marine atmospheric environments through the synergistic design of Sn and Sb, thus not relying on P for corrosion resistance. To ensure the low-temperature impact performance, ductility, and weld safety of the steel plate, this invention strictly controls the P content to no more than 0.01% to ensure overall service reliability.
[0035] S: S is a typical harmful impurity element in steel, readily reacting with Mn to form low-melting-point MnS inclusions. Especially during hot rolling, these inclusions tend to extend along the rolling direction, forming banded structures that become microcrack initiations under fatigue loads or low-temperature impact conditions, severely impairing the steel plate's fatigue resistance, impact toughness, and thickness-direction (Z-direction) properties. Furthermore, S inclusions are also detrimental to the stability and crack resistance of the subsequent weld zone. To ensure good ductility and toughness in the steel plate, this invention further controls the purity of the molten steel based on a low-Mn design, preferably with an S content ≤0.002%. Under certain non-critical service conditions or without Z-direction property (thickness-direction plasticity) requirements, an S content of ≤0.004% is also acceptable.
[0036] Als: As a necessary deoxidizing and grain-refining element added in this invention, the added content is above 0.01%, but exceeding 0.08% can easily cause hot cracking in the cast billet, and at the same time reduce the toughness of the steel. The Als content is controlled between 0.015% and 0.025%.
[0037] The present invention also provides an industrial production method for 32kg-grade offshore wind power steel with high elastic modulus: including smelting, continuous casting, heating, controlled rolling, and controlled cooling;
[0038] (1) Smelting: The present invention is smelted according to the designed alloy composition range, using converter or electric furnace smelting, LF refining, and RH vacuum circulation refining.
[0039] During the smelting process, the content of each alloying element and the purity of the molten steel are precisely controlled. In the LF refining stage, dephosphorization is performed until the P content is no higher than 0.01%, desulfurization until the S content is no higher than 0.002%, and the total oxygen content is controlled below 20 ppm. In the LF refining alloying stage, Sn, Sb, Ti, and B elements are precisely added, with the Sn / Sb mass ratio strictly controlled at 0.60~2.00, and the Ti to B mass ratio ensuring -0.6%≤Ti–2.22×B≤0.6% to generate TiB2 reinforcing particles with an average particle size no greater than 5 μm in situ during steel solidification. Simultaneously, argon blowing is continuously performed for at least 40 minutes during LF refining to promote the homogenization of elements in the molten steel and prevent the coarsening of TiB2 particles, ensuring uniform composition and particle distribution. The RH refining time is ≥30 minutes. At the end of the RH refining process, the alloy composition and temperature of the molten steel are precisely adjusted, and the superheat at tapping is controlled below 25℃ to provide stable metallurgical conditions for subsequent continuous casting processes.
[0040] (2) Continuous casting: Slab continuous casting process is adopted, with protective pouring throughout the continuous casting process. The slab thickness is 250~300mm, the continuous casting speed is controlled within the range of 0.8~1.2m / min, and the liquid level fluctuation in the crystallizer is controlled within ±3mm. Preferably, in order to promote the refinement and uniform dispersion of TiB2 reinforcing particles, an electromagnetic stirrer (M-EMS) is set in the continuous casting crystallizer, with the stirring current controlled at 500~550A and the frequency at 4~7Hz; and in the secondary cooling section, a solidification end electromagnetic stirrer (F-EMS) is used to further optimize the fluidity of the molten steel, avoid grain boundary segregation and TiB2 particle agglomeration and coarsening. The current of the solidification end electromagnetic stirrer F-EMS in the secondary cooling section is 420~500A and the frequency is 3~5Hz. Further optimization involves employing a zoned cooling method in the secondary cooling section; the specific water content in the foot roll section, bending section, and straightening section is controlled at 0.25~0.35L / kg, 0.18~0.28L / kg, and 0.10~0.18L / kg, respectively, and is adjusted in conjunction with the F-EMS system to ensure uniform growth of the solidified shell on the billet, reducing the risk of center segregation, shrinkage cavities, and internal cracks. After the billet exits the mill, a slow cooling device is used to reduce the internal stress gradient, further improving the billet quality and laying the foundation for subsequent controlled rolling and controlled cooling processes.
[0041] (3) Heating: In order to prevent the billet from overheating during the heating process, a low-temperature heating + short-time heat preservation process is adopted. Under the premise of ensuring the homogenization of austenite, the original austenite grain size is controlled. The heating temperature is controlled at 1100~1150℃, the total heating time is controlled at 4~5h, and the furnace exit temperature is controlled at 1080~1120℃.
[0042] (4) Controlled rolling: After heating, the continuously cast billet adopts a three-stage controlled rolling process. The first stage rolling temperature is 980~1050℃, and rolling is carried out in the austenite recrystallization temperature zone. The maximum rolling torque is 3100kNm, and the cumulative reduction rate is ≥45%, including at least one large reduction pass with a single pass reduction rate ≥25%. In this stage, the large reduction deformation in the recrystallization zone is used to break the as-cast structure, promote the deformation nuclei of the austenite phase, refine the γ phase and store energy, create conditions for the subsequent γ→α phase transformation, and improve the uniformity of TiB2 reinforcing particles along the thickness direction. The second stage rolling temperature is 860~890℃, and rolling is carried out in the austenite non-recrystallization temperature zone. The average single pass reduction rate is maintained above 20% to provide more nucleation points and increase the nucleation rate under non-recrystallization conditions, further refine the structure and increase the proportion of ferrite. The third stage of rolling begins at a rolling temperature of 780~800℃, and is rolled in the austenite + ferrite two-phase region. The cumulative reduction rate is controlled at 18%~24%, and the target thickness is achieved.
[0043] (5) Straightening process: The rolled steel plate needs to be straightened to improve the flatness of the steel plate and prevent problems such as warping of the steel plate during the cooling process.
[0044] (6) Controlled cooling: After straightening, the steel plate is placed in a rapid laminar flow cooling system with an average cooling rate of 3~6℃ / s at a temperature of 730~750℃. The reddening temperature is controlled at 580~620℃ to control the composition and size of the phase transformation structure, resulting in a ferrite plus pearlite dual-phase structure. After cooling, the steel plate is subjected to slow cooling for ≥24h.
[0045] Through the above-mentioned smelting, continuous casting and TMCP process control, the uniformity of the microstructure of the final steel plate, the grain size of the reinforcing phase, the grain size and the proportion of each phase are ensured to meet the design requirements. The volume percentage of ferrite is 80%~90%, the average grain diameter of ferrite is about 11~16μm, the interlamellar spacing of pearlite is not greater than 200nm, the volume fraction of TiB2 reinforcing phase particles is not less than 3%, the average particle size is less than 5μm, and the distribution density is 1000~2000 particles / mm².
[0046] The beneficial effects of this invention are as follows:
[0047] (1) This invention adopts a composition design of low C, Mn+Sn-Sb marine atmospheric corrosion resistant alloying + Ti-B in-situ precipitation reinforcement phase + Nb microalloying. On the basis of ensuring high ferrite ratio and good plasticity reserve in the low C, low Mn system, the Sn / Sb mass ratio is controlled to 0.60~2.00 to form a stable and uniform corrosion resistant rust layer, and the microstructure is refined by Nb microalloying.
[0048] (2) During the refining and alloying stage, the mass ratio of Ti and B is precisely controlled (-0.6%≤Ti–2.22×B≤0.6%), and fine and dispersed TiB2 particles are formed in situ in the low C-Mn-Sn / Sb-Nb corrosion-resistant matrix to provide an increase in elastic modulus. The distribution of the reinforcing phase is optimized by combining electromagnetic stirring (M-EMS) in the continuous casting crystallizer and electromagnetic stirring (F-EMS) at the end of the solidification of the second cooling section. Combined with the low temperature homogenization + three-stage controlled rolling + controlled cooling process, the steel plate matrix is finally obtained as a ferrite + pearlite dual-phase structure; the volume fraction of ferrite is 80%~90%, the average grain diameter of ferrite is about 11~16μm, the interlamellar spacing of pearlite is ≤200nm, and TiB2 hard reinforcing particles with a volume fraction greater than 3% are dispersed, with an average particle size of <5μm and a distribution density of 1000~2000 particles / mm².
[0049] (3) In terms of process, the microstructure of steel plate is controlled by the entire process of steelmaking electromagnetic stirring (EMS), low temperature homogenization + short time heat preservation continuous casting billet heating and single-pass large reduction rolling, and finally a 32kg grade high elastic modulus medium and thick plate product with strong plasticity, stable toughness and resistance to marine atmospheric corrosion is obtained.
[0050] (4) The steel plate of this invention has an elastic modulus ≥220 GPa, yield strength ≥320 MPa, tensile strength 440~570 MPa, elongation after fracture ≥21%, Charpy impact energy ≥100 J at -20℃, and the test solution is a 3.5% NaCl solution. The temperature in the salt spray chamber is controlled at 35±2℃, and the salt spray settling velocity is 100 J / 80 cm. 2 Under the condition of a sedimentation rate of 1.5~2 ml per hour on the surface area, the average corrosion rate (g / m²) over a corrosion cycle of 168 hours. 2 The average corrosion rate (g / m³) over 360 hours was 0.72–0.77 h. 2 With a modulus of elasticity (h) of 0.69~0.72, this steel plate combines high elastic modulus, good ductility, low-temperature toughness, and resistance to marine atmospheric corrosion, making it suitable for structures such as the upper and middle sections of offshore wind turbine towers. It meets the requirements for long-term safe operation in marine atmospheric environments. The medium-thick steel plate prepared by this invention for large offshore wind turbines possesses high elastic modulus, resistance to marine atmospheric corrosion, good elongation, and low-temperature toughness, making it suitable for structures such as the upper and middle sections of tower cylinders. Its comprehensive performance meets the requirements for long-term operation of offshore wind turbines. Attached Figure Description
[0051] Figure 1 This is the metallographic microstructure at the 1 / 4 thickness position of Embodiment 1 of the present invention. Detailed Implementation
[0052] The present invention will be further illustrated below through examples.
[0053] The elemental composition of the wind power steel in this embodiment of the invention, by mass percentage, is as follows: C: 0.03%~0.04%, Si: 0.15%~0.25%, Mn: 0.90%~1.00%, Sn: 0.05%~0.12%, Sb: 0.05%~0.10%, Nb: 0.015%~0.025%, Ti: 1.5%~2.5%, B: 0.6%~1.2%, P: ≤0.01%, S: ≤0.002%, Als: 0.015%~0.025%, with the remainder being Fe and unavoidable impurities.
[0054] Furthermore, in the wind power steel, -0.6%≤Ti-2.22×B≤0.6%.
[0055] Furthermore, the Sn / Sb ratio in the wind power steel is 0.60~2.00.
[0056] Furthermore, the microstructure of the wind power steel includes ferrite and pearlite, with fine TiB2 hard reinforcing particles uniformly dispersed throughout the steel.
[0057] Furthermore, the ferrite volume percentage is 80%~90%, the average ferrite grain diameter is about 11~16μm; the pearlite lamellar spacing is ≤200nm; the TiB2 hard reinforcing particles in the wind power steel have a volume fraction ≥3%, an average particle size <5μm, and a distribution density of 1000~2000 particles / mm².
[0058] The steel plate used for offshore wind power has an elastic modulus ≥220GPa, yield strength ≥320MPa, tensile strength 440~570MPa, elongation after fracture ≥21%, Charpy impact energy at -20℃ ≥100J, and a thickness range of 20~60mm.
[0059] According to the component ratio of the technical solution, the embodiments of the present invention carry out smelting, continuous casting, heating, controlled rolling, straightening and controlled cooling.
[0060] Heating: The continuous casting billet is heated at 1100~1150℃ for a total duration of 4~5 hours;
[0061] Controlled rolling: A three-stage controlled rolling process is adopted after the continuous casting billet is heated;
[0062] The first stage of rolling starts at a temperature of 980~1050℃ and has a cumulative reduction rate of ≥45%, including at least one large reduction pass with a single pass reduction rate of ≥25%.
[0063] The second-stage rolling temperature is 860~890℃, and the average single-pass reduction rate is ≥20%.
[0064] The third stage of rolling begins at a rolling temperature of 780~800℃, with a cumulative reduction rate of 18%~24%, and is rolled to the target thickness.
[0065] Controlled cooling: After straightening, the steel plate is initially cooled at 730~750℃ and then enters a rapid laminar flow cooling system at a cooling rate of 3~6℃ / s, with a reddening temperature of 580~620℃. After cooling, the steel plate is subjected to slow cooling for ≥24 hours.
[0066] Furthermore, smelting includes converter or electric furnace smelting, LF refining, and RH refining.
[0067] During the LF refining stage, P ≤ 0.01% and S ≤ 0.002% are controlled, and before the RH refining is completed, the total oxygen in the molten steel is controlled to ≤ 20 ppm.
[0068] Sn, Sb, Ti and B elements are added during the LF refining and alloying stage, and the argon blowing time is ≥40min.
[0069] RH refining time ≥30min, tapping superheat ≤25℃;
[0070] Furthermore, the continuous casting process also includes electromagnetic stirring technology. The continuous casting crystallizer uses electromagnetic stirring M-EMS with a current of 500~550A and a frequency of 4~7Hz; the secondary cooling section uses solidification end electromagnetic stirring F-EMS with a current of 420~500A and a frequency of 3~5Hz.
[0071] Furthermore, the secondary cooling section adopts a zoned cooling method, with the specific water content in the foot roller section, bending section, and straightening section controlled at 0.25~0.35L / kg, 0.18~0.28L / kg, and 0.10~0.18L / kg, respectively; the billet is slowly cooled after exiting the machine.
[0072] The method for testing the microstructure and properties of offshore wind power steel according to the present invention is as follows:
[0073] (1) Statistical method for reinforcing phase: The volume fraction, average size, and distribution density of the TiB2 reinforcing phase in steel were obtained quantitatively through scanning electron microscopy (SEM) images. At magnifications of 5000–10000, more than 10 representative fields of view were randomly selected, with each field of view having a statistical area of no less than 1000 μm². Particle boundaries were identified and automatically counted using image analysis software to obtain the number of particles and their equivalent diameter distribution; the volume fraction was obtained by converting the proportion of the particle's projected area. All results were taken as the average value of all fields of view, and the relative error of the measurement was limited to no more than ±10% to ensure the reliability and repeatability of the results.
[0074] (2) Detection of average pearlite lamellar spacing: The metallographic sample after mechanical grinding, polishing and etching with 4% nitric acid alcohol solution was observed using a scanning electron microscope (SEM). The sampling locations were representative areas at 1 / 4 and 1 / 2 of the steel plate thickness. At a magnification of 10,000 to 20,000, no less than 10 pearlite clusters or representative fields of view were randomly selected, and no less than 5 measurement lines were drawn in each field of view along the direction perpendicular to the pearlite lamellars. The effective length L of each measurement line and the number of lamellar intervals n it traversed were recorded. The lamellar spacing of a single measurement line was calculated according to s=L / n, where L was converted to nm according to the image scale. No less than 50 effective lamellar spacing data were collected for each example. Areas that were obviously non-pearlite, areas with severe lamellar bending and areas with incomplete image edges were removed. The arithmetic mean was taken as the average pearlite lamellar spacing, and the relative error of the measurement was controlled within ±10%.
[0075] (3) Elastic modulus testing: The method specified in GB / T 228.1-2021 or ASTM E111-17 shall be adopted. A standard tensile specimen (parallel length 50 mm, diameter 12.5 mm) in the rolling direction shall be taken and stretched at a loading rate of 2 mm / min under room temperature conditions using an extensometer with an accuracy of 0.5 or higher. The elastic modulus shall be calculated based on the slope of the initial linear segment of the stress-strain curve, and the average value of 3 parallel specimens shall be taken as the result.
[0076] (4) Marine atmospheric corrosion resistance test: An accelerated corrosion test using laboratory salt spray was conducted to simulate a marine atmospheric environment. The embodiments of this invention were subjected to accelerated corrosion tests, with a 40mm thick DH32 steel plate used as a comparative example. The test solution was a 3.5% NaCl solution, the temperature inside the salt spray chamber was controlled at 35±2℃, and the salt spray settling velocity was [value missing] per 80cm [unit missing]. 2 The surface area settles at 1.5~2 ml per hour. Corrosion cycle nodes are set at 168h and 360h. After accelerated corrosion, the average corrosion rate (g / m²) is calculated by measuring the weight loss method. 2 •h) Evaluate the corrosion resistance of the steel plate.
[0077] The composition of the steel in this embodiment is shown in Table 1. The main process parameters for smelting and continuous casting of the steel in this embodiment are shown in Table 2. The zonal cooling parameters for the secondary cooling section of the continuous casting steel in this embodiment are shown in Table 3. The main process parameters for heating and first and second stage controlled rolling of the steel in this embodiment are shown in Table 4. The main process parameters for third stage controlled rolling and controlled cooling of the steel in this embodiment are shown in Table 5. The mechanical properties of the steel in this embodiment are shown in Table 6. The marine atmospheric corrosion resistance rates (g / m³) of the steel in this embodiment and the comparative steel are also shown. 2 (h) See Table 7. The microstructure of steel in the embodiments of the present invention is shown in Table 8.
[0078] Table 1. Composition (wt%) of steel in embodiments of the present invention
[0079] 1 0.034 0.22 0.94 0.09 0.06 0.021 2.0 0.82 0.018 1.50 0.180 2 0.039 0.16 0.98 0.06 0.09 0.017 1.7 0.95 0.024 0.67 -0.409 3 0.031 0.25 0.91 0.11 0.08 0.024 2.4 1.05 0.016 1.38 0.069 4 0.037 0.19 1.00 0.07 0.05 0.020 1.6 0.70 0.021 1.40 0.046 5 0.033 0.24 0.96 0.10 0.10 0.015 2.2 1.20 0.025 1.00 -0.464 6 0.040 0.18 0.92 0.05 0.07 0.025 2.5 0.90 0.019 0.71 0.502 Comparative Example 0.10 0.25 1.48 - - 0.028 0.012 - 0.035 - -
[0080] In the steel composition of this invention embodiment: P: ≤0.01%, S: ≤0.002%, N: ≤0.0030%, O: ≤0.0020%.
[0081] Table 2 Main process parameters for steel smelting and continuous casting in the embodiments of the present invention.
[0082] 1 40 31.4 25 250 500 7 420 4 1.1 2 50 35.6 21 250 550 4 500 3 0.8 3 50 33.8 22 250 550 6 480 3 0.9 4 45 32.5 24 250 500 5 450 5 0.9 5 50 36.2 21 300 550 6 470 4 1.0 6 45 34.1 23 300 500 7 430 5 1.0
[0083] Table 3. Zoned cooling parameters for the secondary cooling section of continuous casting steel according to embodiments of the present invention.
[0084] 1 0.27 0.21 0.13 2 0.34 0.26 0.17 3 0.29 0.23 0.14 4 0.31 0.19 0.11 5 0.33 0.25 0.16 6 0.26 0.22 0.12
[0085] Table 4. Main process parameters for steel heating and one- and two-stage controlled rolling in the embodiments of the present invention.
[0086] 1 1100 4.5 1018 47 30 889 25 2 1150 4.5 1022 49 28 881 24 3 1140 4.5 1013 46 26 877 23 4 1150 4.5 1031 45 25 871 22 5 1130 5.0 1048 52 34 866 26 6 1120 5.0 1032 50 32 861 24
[0087] Table 5. Main process parameters for three-stage controlled rolling and controlled cooling of steel in the embodiments of the present invention.
[0088] 1 794 781 22 750 6 619 24 2 795 775 18 744 5 611 24 3 790 773 21 741 5 602 25 4 786 767 19 735 4 591 25 5 782 771 23 732 4 586 26 6 781 763 20 730 4 582 26
[0089] Table 6 Mechanical properties of steel in the embodiments of the present invention
[0090] 1 20 223 374 522 27 128 2 28 221 398 548 23 108 3 40 227 366 512 28 132 4 48 220 402 552 22 104 5 52 225 379 528 26 119 6 60 224 391 540 24 114 Comparative Example 40 206 353 504 28 221
[0091] Table 7. Marine atmospheric corrosion resistance rates (g / m³) of the steels in the embodiments of the present invention and the comparative steels. 2 ·h)
[0092] 1 0.7428 0.6964 2 0.7563 0.7091 3 0.7246 0.6852 4 0.7685 0.7184 5 0.7319 0.6907 6 0.7598 0.7126 Comparative Example 0.9847 0.9161
[0093] Table 8. Steel microstructure of embodiments of the present invention
[0094] 1 88 13.2 171 3.4 3.9 1760 2 86 14.1 182 3.3 4.2 1695 3 89 12.6 154 3.8 3.6 1940 4 83 13.8 168 3.2 4.7 1588 5 87 12.9 159 3.7 4.1 1872 6 85 13.0 176 3.5 3.8 1810
[0095] The mechanical properties of the steel in this embodiment of the invention were tested according to GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Test at room temperature" and GB / T 229-2020 "Metallic materials, Charpy impact test method". The elastic modulus was calculated using the method specified in GB / T 228.1-2021 or ASTM E111-17, by the slope of the initial linear segment of the stress-strain curve, and the result was taken as the average value of three parallel specimens.
[0096] In this embodiment of the invention, the corrosion resistance testing of steel was conducted using a laboratory accelerated salt spray corrosion test to simulate a marine atmospheric environment. An accelerated corrosion test was performed on the embodiment of the invention, and a 40mm thick DH32 steel plate was used as a comparative example. The test solution was a 3.5% NaCl solution, the temperature inside the salt spray chamber was controlled at 35±2℃, and the salt spray settling velocity was [value missing] per 80cm. 2 The surface area settles at 1.5~2 ml per hour. Corrosion cycle nodes are set at 168h and 360h. After accelerated corrosion, the average corrosion rate (g / m²) is calculated by measuring the weight loss method. 2 •h) Evaluate the corrosion resistance of the steel plate.
[0097] In this embodiment of the invention, the microstructure of steel was detected using an optical microscope and a scanning electron microscope (SEM). The ferrite volume fraction and grain size were determined according to GB / T 6394-2017. The volume fraction, average size, and distribution density of TiB2 reinforcing phase particles were obtained through quantitative analysis of SEM images. At least 10 fields of view were randomly selected at magnification of 5000–10000x, with each field having a statistical area ≥1000 μm². The results were averaged, and the measurement error was controlled within ±10%. The average spacing of pearlite lamellae was determined using the SEM scale calibration and vertical lamellar line intercept method described above. At least 50 effective spacing data were collected for each embodiment, and the arithmetic mean was taken.
[0098] The offshore wind power steel plate produced using this invention has a ferrite + pearlite dual-phase microstructure, with a ferrite volume fraction of 80%~90%, an average ferrite grain diameter of 11~16μm, and a pearlite lamellar spacing ≤200nm. It also contains dispersed TiB2 hard reinforcing particles with a volume fraction greater than 3%, an average particle size <5μm, and a distribution density of 1000~2000 particles / mm². The steel plate of this invention has an elastic modulus ≥220GPa, yield strength ≥320MPa, tensile strength 440~570MPa, elongation after fracture ≥21%, and Charpy impact energy ≥100J at -20℃. It combines high elastic modulus, good ductility, low-temperature toughness, and resistance to marine atmospheric corrosion, making it suitable for the upper and middle sections of offshore wind turbine towers and other structures, meeting the requirements for long-term safe service in marine atmospheric environments.
[0099] To illustrate the present invention, the present invention has been appropriately and sufficiently described above through embodiments. The above embodiments are only for illustrating the present invention and are not intended to limit the present invention. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Any modifications, equivalent substitutions, improvements, etc., should be included within the protection scope of the present invention. The patent protection scope of the present invention should be defined by the claims.
Claims
1. A 32kg grade offshore wind power steel with high elastic modulus, characterized in that, The elemental composition of the wind power steel, by mass percentage, is as follows: C: 0.03%~0.04%, Si: 0.15%~0.25%, Mn: 0.90%~1.00%, Sn: 0.05%~0.12%, Sb: 0.05%~0.10%, Nb: 0.015%~0.025%, Ti: 1.5%~2.5%, B: 0.6%~1.2%, P: ≤0.01%, S: ≤0.002%, Als: 0.015%~0.025%, with the remainder being Fe and unavoidable impurities.
2. The 32kg grade offshore wind power steel with high elastic modulus according to claim 1, characterized in that, In the steel used for wind power, -0.6%≤Ti-2.22×B≤0.6%.
3. The 32kg grade offshore wind power steel with high elastic modulus according to claim 1, characterized in that, The Sn / Sb ratio in the wind power steel is 0.60~2.
00.
4. The 32kg grade offshore wind power steel with high elastic modulus according to claim 1, characterized in that, The microstructure of the wind power steel matrix includes ferrite and pearlite, and TiB2 hard reinforcing particles are dispersed in the matrix.
5. The 32kg grade offshore wind power steel with high elastic modulus according to claim 4, characterized in that, The ferrite volume percentage is 80%~90%, the average ferrite grain diameter is 11~16μm; the pearlite lamellar spacing is ≤200nm; the TiB2 hard reinforcing particles in the wind power steel have a volume fraction of ≥3%, an average particle size of <5μm, and a distribution density of 1000~2000 particles / mm².
6. The 32kg grade offshore wind power steel with high elastic modulus according to claim 1, characterized in that, The steel plate for wind power has an elastic modulus ≥220GPa, yield strength ≥320MPa, tensile strength 440~570MPa, elongation after fracture ≥21%, Charpy impact energy at -20℃ ≥100J, and a steel plate thickness of 20~60mm.
7. A method for producing 32kg grade offshore wind power steel with high elastic modulus as described in any one of claims 1-6, characterized in that, This includes smelting, continuous casting, heating, controlled rolling, and controlled cooling; Heating: The continuous casting billet is heated at 1100~1150℃ for a total duration of 4~5 hours; Controlled rolling: A three-stage controlled rolling process is adopted after the continuous casting billet is heated; The first stage of rolling starts at a temperature of 980~1050℃ and has a cumulative reduction rate of ≥45%, including at least one large reduction pass with a single pass reduction rate of ≥25%. The second-stage rolling temperature is 860~890℃, and the average single-pass reduction rate is ≥20%. The third stage of rolling begins at a rolling temperature of 780~800℃, with a cumulative reduction rate of 18%~24%, and is rolled to the target thickness. Controlled cooling: Start cooling temperature 730~750℃, enter the rapid laminar flow cooling system, cooling rate 3~6℃ / s, reddening temperature 580~620℃; after cooling, the steel plate is slowly cooled for ≥24h.
8. The method for producing 32kg grade offshore wind power steel with high elastic modulus according to claim 7, characterized in that, Smelting includes converter or electric furnace smelting, LF refining, and RH refining; During the LF refining stage, P ≤ 0.01% and S ≤ 0.002% are controlled, and before the RH refining is completed, the total oxygen in the molten steel is controlled to ≤ 20 ppm. Sn, Sb, Ti and B elements are added during the LF refining and alloying stage, and the argon blowing time is ≥40min. RH refining time ≥30min, tapping superheat ≤25℃.
9. A method for producing 32kg-grade offshore wind power steel with high elastic modulus according to claim 7, characterized in that, The continuous casting process also includes electromagnetic stirring technology. The continuous casting crystallizer uses electromagnetic stirring M-EMS with a current of 500~550A and a frequency of 4~7Hz; the second cooling section uses solidification end electromagnetic stirring F-EMS with a current of 420~500A and a frequency of 3~5Hz.
10. A method for producing 32kg-grade offshore wind power steel with high elastic modulus according to claim 7, characterized in that, The secondary cooling section adopts a zoned cooling method, with the specific water content in the foot roller section, bending section, and straightening section controlled at 0.25~0.35L / kg, 0.18~0.28L / kg, and 0.10~0.18L / kg, respectively; the billet is slowly cooled after exiting the machine.
Citation Information
Patent Citations
EH32 class steel for marine engineering with high ductility and manufacturing method of EH32 class steel plate for marine engineering with high ductility
CN110846554A
Large-piece-weight extra-thick steel for offshore wind power and production method thereof
CN111676424A
Marine wind power steel with high fracture toughness and low aging sensitivity and production method thereof
CN111809117A
A high-elastic modulus age-hardening high-speed steel material and its preparation method
CN114686783B